1988
DOI: 10.1007/bf01329346
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the dynamic-mechanical properties of solids from a cooperative model for stress relaxation

Abstract: For many solid materials the stress relaxation process obeys the universal relation F = -(da/d In t)max = (0.1 -t-0.01) ((70 --0"i) , regardless of the structure of the material. Here a denotes the stress, t the time, a o the initial stress of the experiment and (7 i the internal stress. A cooperative model accounting for the similarity in relaxation behaviour between different materials was developed earlier. Since this model has a spectral character, the concepts of linear viscoelasticity are used here to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1993
1993
1993
1993

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…the slope at the inflection point of the normalized stress relaxation curve represented as a function of In t is equal to -(0.10 k 0.01). This empirical result has been recently explained by a two-level cooperative model [45] leading to the normalized transient function of the MAE given in (21).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…the slope at the inflection point of the normalized stress relaxation curve represented as a function of In t is equal to -(0.10 k 0.01). This empirical result has been recently explained by a two-level cooperative model [45] leading to the normalized transient function of the MAE given in (21).…”
Section: Discussionmentioning
confidence: 67%
“…In this case it results w(x) = x -In [In (e) + 11 P) (45) which is represented in Fig. 4c, for different values of 8.…”
Section: Discussionmentioning
confidence: 97%
“…In ref. [15] it is shown that agreement between the experimental values of tan6 and those calculated from the cooperative model is rather good in the case of high density polyethylene (HDPE) at room temperature.…”
Section: Similarity Of the Stress Relaxation Process In Varlous Solidsmentioning
confidence: 94%
“…Assuming that the concepts of linear viscoelasticity are applicable the storage and loss moduli E1(w) and E"(w), can be evaluated from and where w is the angular frequency. This evaluation can be performed numerically but useful analytical approximations of E9(w) and Elf( U) are derived in ref [15]…”
mentioning
confidence: 99%